Initial Study of Factors on Green Supply Chain Management, Green Supplier Strategy and Work System Performance - Mohamed, Norhafiza (International Journal of Integrated Engineering, 2020)
This paper aims to explore the level of green supplier, manufacturing performance, environmental actions and customer activities in implementing green supply chain initiatives. Besides, the relationship between environmental actions and customer activities towards manufacturing performance also been investigated. In this study, the data was collected using questionnaire-based survey among Malaysian manufacturing firms. Next, the data was analysed using factor analysis. The results shows that the manufacturing performance through the implementation of green supply chain management has a positive relationship to environmental action and customer activities.